﻿Specificity of clinical trials of some osteoporosis medicines - Stefka Ivanova; Valentina Petkova (Pensoft Publishers, 2022)
Clinical trials of medicinal products related to the prevention and treatment of osteoporosis cover all activities, operations, methods and means for obtaining summary data and their interpretation in order to reveal the nature of the procedures, as well as certain relationships and dependencies of interest imposed the relevant study. The main objectives of the analysis are to characterize the relationships and dependencies, to measure the significance of these relationships, to model statistically significant relationships and dependencies. An important condition for conducting the statistical analysis is that the data are comparable, i.e. to be based on unambiguously defined features and criteria for their internal content. Objective: This work covers a documentary analysis of conducted clinical trials of drugs for the treatment of osteoporosis, as well as an analysis of the conducted clinical trials of the drug. Denosumab. Methods: Gathering primary empirical information, allowing for: objectification of certain facts; for retrospective study of events and phenomena in a long period; allows to determine the direction of development of the process of clinical trials and processes. The applied statistical analysis covers activities, operations, methods and means for obtaining summary data and for their interpretation in order to reveal the nature of the procedures, as well as certain connections and dependencies. Results: Studies show that clinical trials of osteoporosis products have the following limitations: gender differentiation - although the disease occurs in both sexes, studies in female patients are more common, patients are required to are in menopause, in some studies it is required as including criteria - the presence of a fracture due to osteoporosis, the age characteristic of patients is on average 45-80 years. All analyzed drugs show a positive effect on the state of bone density and bone structure. Conclusion: All analyzed medicinal products show a positive effect on the state of bone density and bone structure but the process is irreversible, so early prevention associated with early diagnosis would lead to earlier treatment measures in the early stages of the disease, which in turn, it would lead to long-term savings in indirect and difficult-to-estimate costs for society as a whole.